THE EFFECT OF LEARNING APPROACH AND THINKING ABILITY ON MATHEMATIC LEARNING OUTCOMES OF GRADE 5 AT SD NEGERI KOTA BINJAI - Saudur Yusmi Silalahi; Harun Sitompul; R. Mursid R. Mursid (Sensei International Journal of Education and Linguistic, 2021)
The purpose of this research was to determine : (1) the Mathematical learning outcomes of primary students taught by Realistic Mathematics Approach and Scientific Approach; (2) the differences between the learning outcomes of students who have high abstract thinking ability and students with low abstract thinking ability; (3) the interaction between learning approach and abstract thinking ability on students' Mathematical learning outcomes. The population of this research was all grade 5 of SD Negeri 028289 and SD Negeri 025282 Kota Binjai. There are 4 classes of grade 5, with the total number of students being 98. Cluster Random Sampling was used to find the total sample, and this research sample consisted of 48 students. The Measurement of Mathematics learning outcomes instrument was an objective test with four possible answers, consisting of 26 items that have been tested the validity and reliability. To obtain data on students' creative thinking ability was done by using a questionnaire tested for validity and reliability. Point Biserial Correlation Formula was used to analyze the Mathematical learning outcome, and Product Moment Formula was used to analyze the abstract thinking ability. The research method was Quasi experiment with 2 x 2 factorial design. The technique of data analysis using ANOVA two ways at the significance level = 0.05. Before the data is analyzed using ANOVA, tdata distribution data should be normal and homogeneous. The Lilifors Provision measures the Normality of data, and the homogeneity of data was measured based on the Fisher and Barlett Test. Based on the results, the researcher obtained that: (1) the Mathematics learning outcomes of students taught by Realistic Mathematics Approach were higher than the mathematics learning outcomes of students taught by Scientific Approach with Fcount = 8.56 > Ftable = 4.06; (2) the Mathematics learning outcomes of students with high abstract thinking ability were higher than students with low abstract thinking ability with Fcount = 20.4 > Ftable = 4.06 ; (3) there is an interaction between learning approach and creative thinking ability on students' Mathematical learning outcomes with Fcount = 7.58 > Ftable = 4.06. From the data analysis, it can be concluded that using the Realistic Mathematics Approach in learning Mathematics is more effective for students with high abstract thinking ability. This is also a good opportunity for students with low abstract thinking ability to increase their ability. The implication of this research is to appoint Mathematical teachers to apply the Realistic Mathematics Approach in teaching Mathematics and recognize students' characteristics like abstract thinking ability.